2004
DOI: 10.1017/s0022112004009401
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of scalar and velocity field evolution in turbulent crossflowing jets

Abstract: Simultaneous planar laser-induced fluorescence (PLIF) and particle image velocimetry (PIV) yield measurements of two-dimensional jet fluid concentration and velocity fields in turbulent crossflowing jets. The jet-to-crossflow velocity ratio is $r = 5.7$ and the jet exit Reynolds number is approximately 5000. The measurements are focused on the developing region of the flow. Two flow configurations are studied, one in which the jet nozzle is flush with the tunnel wall and the other where the nozzle protrudes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
130
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 27 publications
24
130
3
Order By: Relevance
“…The curves are double-peaked due to large gradients on both windward and leeward side. The windward peak is slightly stronger than the leeward peak, consistent with the results of Su and Mungal [15]. The double-peaked rms profiles are evident in experiment and computation.…”
Section: Turbulence Statisticssupporting
confidence: 88%
See 3 more Smart Citations
“…The curves are double-peaked due to large gradients on both windward and leeward side. The windward peak is slightly stronger than the leeward peak, consistent with the results of Su and Mungal [15]. The double-peaked rms profiles are evident in experiment and computation.…”
Section: Turbulence Statisticssupporting
confidence: 88%
“…Conceivable reasons for these differences between experiments and computations are discussed above. [15]. The turbulent scalar flux < v c > is negative below and positive above jet.…”
Section: Turbulence Statisticsmentioning
confidence: 98%
See 2 more Smart Citations
“…Reasonable agreement was found with the data of Smith & Mungal (1998). Su & Mungal (2004) have have reported on simultaneous measurements of velocity and scalar fields in transverse jets. Other studies of turbulent mixing in transverse jets with additional complexity have been reported, e.g.…”
Section: Introductionsupporting
confidence: 86%